Characterization of Plant-Parasitic-Nematode Communities Associated with three Species used in Hedges in Western Niger and their Susceptibility to Meloidogyne Javanica - Adamou, Haougui; Etienne, Sarr; Hamidou, Balde; Ali, Doumma; Toudou, Adam (Asian Journal of Agriculture and Rural Development, 2013)
A study was undertaken in three important vegetable producing areas to determine the plant-parasitic nematodes associated with hedge trees and a pot experiment was conducted to assess hedge trees (Acacia senegal, Bauhinia rufescens and Prosopis juliflora) behavior to the root-knot-nematode, Meloidogyne javanica. Soil and roots analysis revealed the presence of 10 genera of plant-parasitic nematodes, including M. javanica. The behavior test seems to indicate that all three plants were susceptible to Meloidogyne javanica with root gall index ranging from 1 to 2.8, and nematode multiplication rate ranging from 2.78 to 5.70.